STUDENTS’ PERCEPTION ON THE USE OF YOUTUBE AS LEARNING ENGLISH MEDIA IN SPEAKING AT THE 9TH GRADE OF MTS MA’ARIF NU 01 KROYA - Fitri Damayanti; Desi Wijayanti Marufah (Journal of Applied Linguistics (ALTICS), 2021)
In the modern era, technology can help the teaching and learning process. There are many teachers and students that used YouTube to help them in the teaching and learning process. This research aimed to analyze students’ perceptions on the use of YouTube as learning media and analyze the use of YouTube for the lesson in speaking at the 9th grade of MTs Ma’arif NU 01 Kroya. The researcher was used descriptive qualitative research. The data were obtained through questionnaires and interviews. The researcher used triangulation for the trustworthiness of the data. The research subjects included students of the 9th grade. The results of the study of students’ perception on the use of YouTube as learning media in speaking at the 9th grade of MTs Ma’arif NU 01 Kroya, that are: 1) YouTube has advantages as learning media and for lesson speaking such as students can learn speaking directly from native speakers’ videos, so that students can improve their speaking, 2) YouTube also has disadvantages such as trouble when used like bad connection or there were advertisement that disturbed, and students cannot know the mistakes when they learn speaking independently from YouTube. Keywords: Students’ Perception, Learning Media, Teaching Speaking